Personal protective equipment-associated headaches in health care workers during COVID-19: A systematic review and meta-analysis - Ali Sahebi; Naser Hasheminejad; Masoumeh Shohani; Atefeh Yousefi; Somayeh Tahernejad; Azadeh Tahernejad (Frontiers Media S.A., 2022)
IntroductionHealth Care Workers (HCWs) use Personal Protective Equipment (PPE) during the COVID-19 pandemic to protect themselves and prevent the transmission of the disease. The use of PPE, especially respiratory masks, has adverse consequences, including headaches, which have been secondary and unusual. The aim of the present systematic review and meta-analysis study was to investigate the prevalence of PPE-associated headaches in HCWs during COVID-19 pandemic.MethodsThe present review study was performed based on the PRISMA guideline. The protocol of the present study was registered in PROSPERO with the code CRD42022304437. Valid data resources such as Scopus, PubMed, Web of Science, Science Direct, Google Scholar, Embase were used to identify and extract relevant studies. The searches were conducted between the beginning of 2020 and the end of January 2022. A random effects model was used for meta-analysis and I2 index was used to investigate between-study heterogeneity. Data were analyzed using STATA ver. 14.ResultsA total of 539 articles were first identified through initial search and finally 26 final studies were selected to undergo the meta-analysis phase. According to the results of meta-analysis, the prevalence of headache after and before the use of PPE was 48.27% (95% CI: 40.20-56.34, I2 = 99.3%, p = 0 < 001) and 30.47% (95% CI: 20.47-40.47, I2 = 97.3%, p = 0 < 001), respectively.ConclusionThe results of the present study showed that the prevalence of PPE-associated headache in HCWs was relatively high, so, the use of PPE during COVID-19 pandemic can be considered as one of the causes of headache. Therefore, management strategies such as regular screening of HCWs for headaches and regular rest periods without the use of PPE can be effective in reducing the prevalence of headaches.